2008
DOI: 10.1021/ma800677h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis by RAFT and Ionic Responsiveness of Double Hydrophilic Block Copolymers Based on Ionic Liquid Monomer Units

Abstract: Three imidazolium-based ionic liquid (IL) monomers, namely, 3-(1-ethyl imidazolium-3yl)propylmethacrylamido bromide (IL-1), 2-(1-methylimidazolium-3-yl)ethyl methacrylate bromide (IL-2), and 2-(1-ethylimidazolium-3-yl)ethyl methacrylate bromide (IL-3), and methacrylic acid (MAA) were polymerized by the reversible addition fragmentation chain transfer (RAFT) process in methanolic solutions at 70 °C, using either 2-cyanopropyl dithiobenzoate (CTA-1) or (4-cyanopentanoic acid)-4-dithiobenzoate (CTA-2) as chain tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
169
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 65 publications
3
169
0
3
Order By: Relevance
“…BMA [139] MAA [140] MMA [64,141] AEMA [90,142] DEGMA [141] DMAEMA [143] DPAEMA [144] MAA [145] PEGMA [144,[146][147][148] 383 [149] DMAM [150] NIPAM [151] 274 [152,153] 325 [154] 326 [154] APMAM-b-NIPAM [89,152] AEMAM [153] St [155] 274 [153] 275 [153] 285 [156] 286 [156] 289 [157] 292 [158] 304 [140] 305 [140] 331 [159] 329 [140] 327 [157] 380 [160] 391 [161,162] 389 [104] (390) [104] 416 [163,164] MAA-b-280 [145] BMA-b-MPC [139] PEGMA/ 320 [165] PEGMA/344 [165] DEGMA-b-384 [141] MMA-b-384 …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…BMA [139] MAA [140] MMA [64,141] AEMA [90,142] DEGMA [141] DMAEMA [143] DPAEMA [144] MAA [145] PEGMA [144,[146][147][148] 383 [149] DMAM [150] NIPAM [151] 274 [152,153] 325 [154] 326 [154] APMAM-b-NIPAM [89,152] AEMAM [153] St [155] 274 [153] 275 [153] 285 [156] 286 [156] 289 [157] 292 [158] 304 [140] 305 [140] 331 [159] 329 [140] 327 [157] 380 [160] 391 [161,162] 389 [104] (390) [104] 416 [163,164] MAA-b-280 [145] BMA-b-MPC [139] PEGMA/ 320 [165] PEGMA/344 [165] DEGMA-b-384 [141] MMA-b-384 …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
“…[96] N O O 278 [96] O O N N O O MMBL 279 [258] O [124,145] 281 [124] O [197] O F 3 C F 3 C CONH 2 CONH 2 284 [197] [158] 294 [125] N O O N N CN 295 [126] O O O N OH 296 [127] [436] O O O O 299 [317] O O O O O OH 300 [455] [456] TPMMA 302 [92] O O 303 [203] O O S 304 [140] …”
Section: End-functional Polymers and End-group Transformationsunclassified
See 2 more Smart Citations
“…14,15 For example, Waymouth et al 16,17 demonstrated the synthesis of a series of block copolymers containing polystyrene and imidazolium-functionalized polystyrene by nitroxide-mediated polymerization, followed by post-synthetic modification of the chloromethyl groups. Recently, Gnanou et al 18 reported the synthesis of double hydrophilic block copolymers with ionic responsive properties by the reversible addition-fragmentation chain transfer (RAFT) polymerization of methacrylate-type ionic liquids. RAFT polymerization was also employed for the synthesis of block copolymers containing imidazolium and thiazole groups, which showed characteristic magnetic properties.…”
Section: Introductionmentioning
confidence: 99%